Produção de biogás a partir de resíduos de bovinocultura leiteira por meio da codigestão com macrófitas da espécie Salvinia - Lins, Leonardo Pereira (2017)
Milk production in small farms is an important activity in food production but can cause environmental impacts due to the generation of waste that needs to be treated before being disposed of in the environment to avoid contamination of rivers, streams and Streams Contamination of water bodies by these or other residues may lead to increased nutrients and favor the proliferation of algae and macrophytes. The treatment of these residues, from agricultural and livestock activities, can be carried out through anaerobic digestion, which has biogas and biofertilizer as products, in order to reduce environmental impacts. In this work, the objective was to evaluate the potential of biogas production from the biodigestion of residues from the milk production activity, from a small property in the Western Region of Paraná, with the inclusion of Salvinia macrophyte, which is common in the study region. In order to evaluate the biogas production potential, both the bovine effluent and the Salvinia macrophyte were characterized by tests of Total Solids (TS), Fixed Solids (FS) and Volatile Solids (VS). The assays for the evaluation of the Biochemical Methanogenic Potential (BMP) were conducted in batch reactors in the bench scale, considering the bovine effluent and mixtures with the macrophytes, in natura and dehydrated form, at concentrations of 6, 7, 8 and 9 %. The results of the volumetric production of biogas and methane as a function of the mass of volatile solids from the mixtures of 6, 7, 8 and 9% were 286 and 197, 250 and 178, 234 and 162 and 203 and 143 LN.kgSV-1, respectively. When the results of the calorific value obtained for each sample were related, the mixture with 8% of macrophytes was the one with the best result with 5,237 kcal.m-3. The final result was also evaluated by the production of biogas and methane in volume produced per kilogram of fresh mass. Again the mixture with 8% showed the best result, with 12.8 LN of biogas per kilogram of biomass. Therefore, considering a daily production of 600 L of waste, the biogas production estimate of the mixture with 8% was 7.7 Nm³ and that of the bovine effluent is 6.8 Nm³. Although, when this substrate mix has an increase in biogas, when evaluating project implementation costs (such as collection, drying, grinding and storage), as well as the use of the existing system, it is concluded that the implementation of this Scale project is not feasible but may be an index to another form of management.